Veerebradiah Lokesha Reciprocal Status Index pada Komplemen Graf Total Diperumum dari Ring Bilangan Bulat Modulo - Armeyntan, Tata Sutrafia; Turmudi, Turmudi; Jauhari, Mohammad Nafie (Jurnal Riset Mahasiswa Matematika, 2024)
Suppose R is a commutative ring and H is a subset of R. The complement of the generalized total graph is a simple graph with all the elements in R as points and two different points x and y are directly connected if and only if x and y are not elements of H. This study aims to determine the general form of the VLRS index in the generalized total graph complement of the integer ring modulo 2p where p greater than or equal to 3 is the prime number for H the set of zero divisors and H the set of units of the ring integer modulo 2p. The steps in this study are to determine the set of zero divisors and the set of units of the integer ring modulo 2p, determine the distance of each point in the complement of the generalized total graph of the ring of integers modulo 2p, determine the reciprocal state in the complement of the generalized total graph of the ring integer modulo 2p, and determine the VLRS index in the complement of the generalized total graph from the integer ring modulo 2p. The results of this study are related to the general form of the VLRS index on the complement of the generalized total graph of the 2p modulo integer ring where p is a prime number and p is greater than or equal to 3 with H the set of zero divisors and H the set of units of the 2p modulo integer ring.